PSYCHIATRY: MODERN APPROACHES, PROBLEMS, AND DEVELOPMENT PROSPECTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article examines key areas of modern psychiatry, including the etiology and pathogenesis of mental disorders, their classification, diagnostic and treatment methods. Special attention is paid to the development of the biopsychosocial model, the use of neuroimaging, psychopharmacology, and psychotherapeutic approaches. Current issues of stigmatizing mental illnesses, the need to reform the psychiatric care system, as well as the prospects for introducing digital technologies, telepsychiatry, and personalized medicine are highlighted.